Mechanism of Silver Ion Reduction in Concentrated Solutions of Amphiphilic Invertible Polyesters in Nonpolar Solvent at Room Temperature - Voronov, Andriy; Kohut, Ananiy; Vasylyev, Serhiy; Peukert, Wolfgang (Langmuir, 2008)
Fast formation and efficient stabilization of silver nanoparticles from [Ag(NH3)(2)]OH are achieved in concentrated nonpolar solutions of amphiphilic invertible polyesters based on poly(ethylene oxide) (PEO) and aliphatic dicarboxylic acids. Surface-modified silver nanoparticles able to be dispersed in both a polar and nonpolar medium are developed in the form of a ready-to-use colloidal solution with an enhanced silver concentration. The PEO fragments of polyesters form cavities (also called pseudo-crown ester structures) that can bind metal ions. The reduction of bound metal ions proceeds. via oxidation of polyoxyethylene fragments. No chemical reducing agents are necessary in this approach. The polyesters act simultaneously as an efficient reducing agent and stabilizer. The main focus of the present research is to clarify the chemical mechanism of silver ion reduction in amphiphilic polyester solutions. A one-electron reduction mechanism is proposed to explain the formation of silver nanoparticles. The effect of the poly(ethylene oxide) fragment length and the polyester concentration are explored by examining several amphiphilic polyesters.